The Influence of the Human and Economic Index Development Components on the Unemployment Rate in Indonesia - Eka Purwanda (ijd-demos, 2022)
Human development is one indicator of the achievement of economic, social, political, cultural, environmental and welfare development, this must occur in all aspects of life that can encourage better human quality. Human development is a development process that aims to have more choices, especially in income, health, and education. One of the benchmarks can be seen through the Human Development Index. The concept of human development does sound different from the classic concept of development which focuses on economic growth. Human development emphasizes expanding people's choices to live full of freedom and dignity. Human development also talks about expanding the capabilities of individuals and communities to expand their range of choices to fulfil their aspirations. This research is based on descriptive and explanatory research, it is said to be descriptive because this research describes the object to be studied.Furthermore, this study examines the relationship between variables, which is classified as explanatory research, namely research that intends to test and explain the relationship between variables and the dependent variable. The results of this study explain that human resource development is a tiered process in the long term in which various socio-economic factors also contribute to it. The process of human resource development is the interaction of various cross-sectoral components that occur gradually from the traditional period, the development period, to the modern period. The development of human resources in the current era implies that the benefits of growth must directly impact various segments of human life and indirectly be able to actively influence the processes that shape their lives.